INTERNAL FORM OF PHRASEOLOGICAL UNITS WITH THE COMPONENTS OF PRECIOUS STONES AND METALS IN THE ENGLISH LANGUAGE (Scientific journal of the Fergana State University, 2024)
The article analyzes the nature of the internal form of phraseological units of the English language that contain components of precious stones and metals. The purpose of our work is to analyze the nature of the internal form of phraseological units with a component of precious stones and metals in the English language. The following methods were used in the work: the method of component analysis, the etymological method, and the methods of cognitive linguistics. The study of the nature of the relationship between the prototypes of phraseological units and their meaning made it possible to establish that in most cases this connection continues to be transparent and accessible to perception. As a result of studying the nature of the internal form of phraseological units in the English language with a component of precious stones and metals, we can conclude that most of the phraseological units under consideration have a transparent internal form, that is, their meaning is intuitively clear. understandable to native speakers thanks to the logical-semantic connection that is maintained between the components of the phraseological unit and its meaning. In this case, the derivational connection between the prototype of a phraseological unit and the phraseological meaning may be violated for reasons such as the relationship of the designation of a phraseological unit to a name that is not predominant.